Association between the peripheral blood eosinophil counts and COVID-19: A meta-analysis. Issue 23 (11th June 2021) - Huang, Rong; Xie, Liangcai; He, Junpeng; Dong, Hong; Liu, Tianchun
Abstract: Background: The conclusions about the relationship between eosinophil counts and the severity of coronavirus disease 2019 (COVID-19) were controversial, so we updated the evidences and reassessed it. Methods: We searched the PubMed, Cochrane library, Excerpta Medica Database, and Web of Science to compare the eosinophil counts about non-severe disease group (mild pneumonia, moderate pneumonia, non-critical disease and recovery group) and severe disease group (severe pneumonia, critical pneumonia, critical disease and death group) in COVID-19. Results: A total of 1228 patients from 10 studies were included. Compared with non-severe group, severe group had strikingly lower average eosinophil counts (SMD 0.65, 95% confidence intervals [CI] 0.29–1.01; P < .001). The result of subgroup analysis of different countries showed SMD 0.66, 95% CI 0.26–1.06; P < .001. Another subgroup analysis between mild-moderate pneumonia versus severe-critical pneumonia showed SMD 0.69, 95% CI 0.25–1.13; P < .001, and no significant risk of publication bias (Begg test 0.063 and Egger test 0.057) in this subgroup. The heterogeneity was substantial, but the sensitivity analyses showed no significant change when individual study was excluded, which suggested the crediblity and stablity of our results. Conclusions: The eosinophil counts had important value as an indicator of severity in patients with COVID-19. PROSPERO registration number: CRD42020205497.